Life Stories of Social and Environmental Entrepreneurs - Feitosa de Lucena Cavalcante, Roberta; de Sousa Filho, José Milton (Organizações & Sociedade, 2023)
This research aimed to analyze the influence of the antecedents of the behavior of social entrepreneurs (SE) through their life stories. For this, the dimensions of the Theory of Planned Behavior (TPB) were used, which cover personal attitudes, subjective norms, and perceived behavioral control, inaddition to behavioral intention. For this proposition, a basic qualitative, descriptive-exploratory research was carried out, classified as a field study. For data collection, semi-structured interviews were conducted with thirty Brazilian social entrepreneurs, in the form of autobiographical narratives. To analyze the data, the strategies of content analysis and the abductive method were used. In both stages, the New NVivo software was adopted. Among the results obtained, a theoretical model is presented, through dimensions, which emerged from the TPB and from the field research, characterizing these dimensions as predecessors, explaining how the life story, which acts in a transversal way, influences the antecedents of the behavior of social entrepreneurs. This study enables the advancement of discussions and the display of new perspectives on socio-environmental entrepreneurship. It is noted that this investigation contributes to filling a theoretical gap, pointed out in the literature, on the identification of characteristics and trajectories of social entrepreneurs, starting from the life story narratives, from the point of view of the entrepreneur, as a person, and not at an organizational level of institutions.